The validity and reliability of global positioning systems in team sport: a brief review - Scott, M. T. U.; Scott, T. J.; Kelly, V. G. (The Journal of Strength and Conditioning Research, 2016)
The use of global positioning systems (GPS) has increased dramatically over the last decade. Using signals from orbiting satellites, the GPS receiver calculates the exact position of the device and the speed at which the device is moving. Within team sports GPS devices are used to quantify the external load experienced by an athlete, allowing coaches to better manage trainings loads and potentially identify athletes who are overreaching or overtraining. This review aims to collate all studies that have tested either (or both) the validity or reliability of GPS devices in a team sport setting, with a particular focus on (a) measurements of distance, speed, velocities, and accelerations across all sampling rates and (b) accelerometers, player/body load and impacts in accelerometer-integrated GPS devices. A comprehensive search of the online libraries identified 22 articles that fit search criteria. The literature suggests that all GPS units, regardless of sampling rate, are capable of tracking athlete's distance during team sport movements with adequate intraunit reliability. One Hertz and 5Hz GPS units have limitations in their reporting of distance during high-intensity running, velocity measures, and short linear running (particularly those involving changes of direction), although these limitations seem to be overcome during measures recorded during team sport movements. Ten Hertz GPS devices seem the most valid and reliable to date across linear and team sport simulated running, overcoming many limitations of earlier models, whereas the increase to 15Hz GPS devices have had no additional benefit.